The self-care behaviors and health literacy can play important preventive roles in older female osteoporosis - Elahe Malekmirzaei; Azizeh Farshbaf-Khalili; Vahid Pakpour (BMC Women's Health, 2023)
Abstract Background Osteoporosis is a common complication of aging and menopause. Self-care and health literacy are among the factors affecting health status. The purpose of this research was to determine the preventive roles of self-care behaviors and health literacy in older women with osteoporosis. Methods This cross‑sectional analytical research was conducted on 250 postmenopausal women consisting of 125 osteoporotic and 125 healthy people aged 60–70. They were selected by purposive sampling in Tabriz Sina Hospital from September 2021 to December 2021. Data collection instruments were a demographic questionnaire, a Menopausal Self‑Care Questionnaire, and a European Health Literacy Survey Questionnaire. Data were analyzed using SPSS 23 software. Results The mean (SD) total score of self-care in healthy women was 118.97 (19.92) and in women with osteoporosis was 84.7 (14.98) (p < 0.001). Also, healthy women all had sufficient health literacy (100%), but 52.8% of women with osteoporosis had insufficient health literacy. The odds of osteoporosis decreased significantly with the rise in the total score of self-care behaviors [Odds ratio 95% confidence interval (95% CI); p: 0.909 (0.880 to 0.939); p < 0.001] and its subdomains as well as with increasing health literacy level [OR (95% CI); p: 0.322 (0.266 to 0.383); p < 0.001]. There was a significant positive correlation between self-care behaviors and health literacy (r = 0.616, p < 0.001). Conclusions Self-care in aged women is particularly important in reducing the risk of osteoporosis, and empowering women in the field of health literacy is an important factor in improving self-care behaviors and ultimately the health of these people.